Changes in Warfarin Sensitivity During Decompensated Heart Failure and Chronic Obstructive Pulmonary Disease. (September 2015) - del Campo, Michaela; Roberts, Greg
Background: Heart failure (HF) has been associated with an elevated international normalized ratio (INR) in patients on warfarin.Objectives: Compare warfarin sensitivity during hospital admission for HF exacerbation and chronic obstructive pulmonary disease (COPD) exacerbation with admissions unrelated to HF or COPD (controls) as well as during disease stability.Methods: We conducted a case-controlled observational study. Patients admitted to a tertiary teaching hospital for HF exacerbation (n = 37), COPD exacerbation (n = 26), and admissions unrelated to HF or COPD (controls, n = 60) were included. Warfarin sensitivity (INR per daily mg dose of warfarin) at admission was compared to periods of disease stability and also compared between the 3 groups.Results: The increase in warfarin sensitivity at admission was 94% for HF patients ( P < 0.0001), 59% for COPD ( P = 0.003) patients, and 24% for controls ( P = 0.002). HF patients with New York Heart Association (NYHA) class 3 and 4 and NYHA class 1 and 2 experienced changes in warfarin sensitivity of 125% ( P = 0.006) and 50% ( P = 0.13) at admission. HF patients had higher warfarin sensitivity at admission (mean = 1.62 [SD = 1.27]) compared to the control group (0.91 [0.52], P < 0.0001) and COPD group (1.03 [0.79], P = 0.04). and required greater intervention with vitamin K than controls (14% vs 0%, P = 0.007).Conclusion: HF and COPD patients were more sensitive to warfarin during disease exacerbation, with HF exacerbation having the largest impact, resulting in clinically significant management implications.